2021
DOI: 10.3390/econometrics9010009
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Anomalies, Long Memory, and Aggregation

Abstract: Econometric studies for global heating have typically used regional or global temperature averages to study its long memory properties. One typical explanation behind the long memory properties of temperature averages is cross-sectional aggregation. Nonetheless, formal analysis regarding the effect that aggregation has on the long memory dynamics of temperature data has been missing. Thus, this paper studies the long memory properties of individual grid temperatures and compares them against the long memory dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Barreiro et al analyzed the monthly air temperature anomaly time series via ordinal pattern analysis and also detected LTC over EPWP [ 62 ]. Recently, Vera-Valdés investigated LTC in global monthly temperature anomalies by analyzing the autocovariance function and spectral density [ 63 ] and found that the degree of LTC were influenced by the long term dynamics of temperature anomalies in the Tropics. In this study, the imprint of ENSO on LTC of SAT anomaly time series is also very obvious [ 6 , 64 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Barreiro et al analyzed the monthly air temperature anomaly time series via ordinal pattern analysis and also detected LTC over EPWP [ 62 ]. Recently, Vera-Valdés investigated LTC in global monthly temperature anomalies by analyzing the autocovariance function and spectral density [ 63 ] and found that the degree of LTC were influenced by the long term dynamics of temperature anomalies in the Tropics. In this study, the imprint of ENSO on LTC of SAT anomaly time series is also very obvious [ 6 , 64 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Climate data have also been shown to possess long-range dependence. Several authors have argued that aggregation may be the reason behind the presence of long-range dependence in temperature data; see Baillie and Chung (2002);Gil-Alana (2005); Mills (2007);Vera-Valdés (2021a). Figure 6 shows an example using temperature data.…”
Section: Applicationmentioning
confidence: 99%
“…Besides the R/S analysis, many other methods have been proposed for estimating the parameter H, such as the detrended fluctuation analysis (DFA), periodogram method, aggregated variance method, structure function method, etc. With these methods, fractal and multifractal properties in different climatic variables have been investigated by many researchers (Caballero et al 2002;Vyushin and Kushner 2008;Yuan et al 2014;Qiu et al 2020;Vera-Valdés 2021).…”
Section: Introductionmentioning
confidence: 99%